2013
DOI: 10.3928/01477447-20130523-20
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Change in Pelvic Posterior Tilt After THA

Abstract: In total hip arthroplasty, steep cup inclination should be avoided because it increases the risk of edge loading. Pelvic posterior tilt should be carefully monitored because it increases cup inclination and anteversion, leading to edge loading or impingement. The authors evaluated how much the pelvic tilt angle changes from the supine position referenced in planning for cup orientation preoperatively to the standing position 1 year after total hip arthroplasty (Δref). The pelvic tilt angle was measured in 124 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 20 publications
2
45
1
Order By: Relevance
“…15,25,26 In addition, a more proximal knee joint would cause the pelvis to increase forward tilt during the heelstrike phase of gait, 27 an established cause of hip osteoarthritis. [28][29][30][31][32][33] Song et al 15 showed increased mechanical work during gait for patients with limb-length discrepancies >3 cm, perhaps by a similar mechanism, decreasing the distance between the knee and hip joint relative to the distance between the knee and ankle joint.…”
Section: Discussionmentioning
confidence: 94%
“…15,25,26 In addition, a more proximal knee joint would cause the pelvis to increase forward tilt during the heelstrike phase of gait, 27 an established cause of hip osteoarthritis. [28][29][30][31][32][33] Song et al 15 showed increased mechanical work during gait for patients with limb-length discrepancies >3 cm, perhaps by a similar mechanism, decreasing the distance between the knee and hip joint relative to the distance between the knee and ankle joint.…”
Section: Discussionmentioning
confidence: 94%
“…We could not predict the relatively rare occurrence of a large change in pelvic tilt, which would confound tilt-adjusted component position. The pelvis is a dynamic link between the axial and appendicular skeleton, and studies have demonstrated the importance of taking into account the condition of the spine for preoperative planning of acetabular component position throughout a range of functional positions [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Thirdly and lastly, no lumbosacral comorbidities are mentioned, except the absence of instrumented lumbosacral fusions that were considered an exclusion criterion. However Kyo et al demonstrated that disc space narrowing, spondylolisthesis and pre-existing compression fractures are predictive factors for posterior pelvic tilt after THA [7]. What about the distribution of these spine diseases in the reported series?…”
mentioning
confidence: 86%